Developmental delay and its associated factors among children of 9 months and of 18 months attending primary health facilities in an urban resettlement area of East Delhi - Bhavana Verma; Pragti Chhabra; Amir K. Maroof; Anju Aggarwal (Journal of Family Medicine and Primary Care)
Background: Early identification of developmental delay in children can help in making early intervention for its management. Routine developmental screening is not being practised in India due to lack of trained field workers, lack of awareness among parents and lack of feasible assessment screening tool. There is lack of studies that focuses on home environment provided to the children as it is associated with developmental delay. Methods: A cross sectional study was conducted in immunization clinic of two Maternal and Child Welfare (MCW) centres of Nand Nagari, an urban resettlement colony in East Delhi among children of 9 months and 18 months of age. New Delhi Development Status Questionnaire (ND-DSQ) was used for assessment of developmental status. Data on socio-demographic profile, home stimulation of the child and anthropometric measurements including weight, height was collected. Chi-square test was used for univariate analysis and binary logistic regression was used to find out the predictors of developmental delay. Results: The prevalence of DD was found to be 17.7% in children 9 m of age, and 10% in 18 m. On univariate analysis preterm gestation, low-birth weight of the child, lower mother’s education status and presence of complications at birth were significantly associated with developmental delay. The independent predictors of DD were presence of complications at birth, preterm gestation, lower mother’s education status and underweight children. Conclusion: This study reports a higher prevalence of DD. More follow up studies on DD is needed to see the course of achievement of developmental milestones. Screening for developmental milestones can be done during visit for immunization.